Reduction in occipital cortex gamma-aminobutyric acid concentrations in medication-free recovered unipolar depressed and bipolar subjects. - Bhagwagar, Z; Wylezinska, M; Jezzard, P; Evans, J; Ashworth, F; Sule, A; Matthews, P; Cowen, P (2007)
BACKGROUND: Studies using proton magnetic resonance spectroscopy (MRS) have indicated that unmedicated, acutely depressed patients have decreased levels of gamma-aminobutyric acid (GABA) in occipital cortex. Cortical levels of glutamate (Glu) may be increased, although these data are less consistent. The aim of this study was to use MRS to determine whether changes in GABA and Glu levels were present in patients with mood disorders who had recovered and were no longer taking medication. METHODS: An [1H]-MRS was used to measure levels of GABA, of the combined concentration of Glu and glutamine (Gln), and of N-acetylaspartate (NAA) in occipital cortex in medication-free, fully recovered subjects with a history of recurrent unipolar depression (n = 15), bipolar disorder (n = 16), and a group of healthy controls (n = 18). RESULTS: Occipital levels of GABA and NAA were significantly lower in recovered depressed and bipolar subjects than in healthy controls, whereas Glu +Gln concentrations were higher. CONCLUSIONS: Our data suggest that recovered unmedicated subjects with a history of mood disorder have changes in cortical concentrations of GABA, NAA, and Glu +Gln. These biochemical abnormalities may be markers of a trait vulnerability to mood disorder, rather than neurochemical correlates of an abnormal mood state.